2016
DOI: 10.1149/2.0011705jes
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Oxide Nanoparticles Immobilized on MWCNTs/PANI Composite Film as an Electron Transfer Facilitator for Horseradish Peroxidase: Direct Electron Transfer and H2O2Determination

Abstract: In this paper, we developed a new method for immobilization of horseradish peroxidase (HRP) on Nano-NiO/ MWCNTs/PANI composite film, which can effectively promote the direct electron transfer and electrocatalysis of enzyme in neutral solution. This composite film modified electrode was systematically investigated by altering the thickness of composite film, pH value of solution, and the mass ratio of MWCNT to NiO nanoparticles. The study showed that the effective immobilization of horseradish peroxidase on Nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…In this sense, Ran et al [20] fabricated a sensor by MWCNT and chitosan doped poly(aminobenzene sulfonic acid) to determine serotonin levels. Polyaniline (PANI) is a good candidate for composites with multiwalled carbon nanotubes due to its electrical and optical properties, good environmental stability, and facile synthesis [24]. Another study [6] also determined serotonin using a poly(3,4ethylenedioxy pyrrole)-single walled CNT modified glassy carbon electrode (GCE).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Ran et al [20] fabricated a sensor by MWCNT and chitosan doped poly(aminobenzene sulfonic acid) to determine serotonin levels. Polyaniline (PANI) is a good candidate for composites with multiwalled carbon nanotubes due to its electrical and optical properties, good environmental stability, and facile synthesis [24]. Another study [6] also determined serotonin using a poly(3,4ethylenedioxy pyrrole)-single walled CNT modified glassy carbon electrode (GCE).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and detection limit of the Ni electrode for H 2 O 2 detection were compared with those obtained at other similar sensors, essentially constructed on nanostructured on Ni/NiO materials (Table 3). It can be observed that with two exceptions 33,34 which involve enzyme-based electrodes, higher sensitivity is reported for NiO/ITO, 32 which operates at a more negative potential than the Ni/Au electrode presented in this work.…”
Section: F M Z Zmentioning
confidence: 56%
“…Figure 2 (b,c) is shown that the FESEM images of the nickel oxide nano hollow sphere diameter ranges from 200-300 nm in size, with wall diameter are 30-40 nm [25]. The size can be controlled by the size of the carbon sphere, time, and temperature and concentration of nickel chloride.…”
Section: The Fesem and Hrtem Images Of Carbon And Nio Nano Hollow Spherementioning
confidence: 95%